Ultimate Southern Fiber Management System - NOR FAUZI, MUHAMMAD FARIS; SULAIMAN, NUR LIYANA (Applied Information Technology And Computer Science, 2025)
The Ultimate Southern Fiber Management System (MS) aims to solve the staff management challenges faced by Ultimate Southern Fiber in the boat industry. The company's current methods for payroll, attendance, and employee data management are manual, leading to errors and delays. To address this, the project designs a web-based system using an object-oriented approach and undergoes both alpha and beta testing. The system development will follow the Waterfall methodology, which includes requirements analysis, design, implementation, testing, deployment, and maintenance. The Ultimate Southern Fiber Management System (MS) likely uses a client-server architecture for administrators and staff to interact with the system. Technologies used include PHP, Visual Studio Code, Apache, and MySQL via XAMPP. The result of user acceptance testing (UAT) confirmed the system’s functionality, with 90% success in alpha testing and 61.2% in beta testing. The significance of MS is helping the company stay competitive in the boat industry.